Productivity enhancement of Evacuated Tubes solar still of different water depth: Thermal modelling and an Experimental analysis. Issue 1 (February 2021) - More, Sunil; Daniel, Joseph
Abstract: In this research article, the author has conducted the comparative thermal experimental analysis and investigation on Conventional still and Modified Evacuated Tubes solar still with different water volume of 30 and 50 Litre in Basin, in respect of Energy Balance Equation. The various variable elements have been taken into account and duly calculated for both the stills i.e. active still and passive still, based on thermal modelling. The variables calculated comprise inner glass surface temperature, distillate yield, basin water temperature etc. The entire study has been carried out at Akison's Solar Equipments Pvt. Ltd., Shirwal, Maharashtra, India (latitude18.14° N: longitude 73.97° E), with adequate instrumental infrastructure setup appropriate for the purpose. The investigation concluded that there is substantial escalation of. 242% and 246% at 0.03 and 0.05m of water depth respectively in the yields obtained from Modified Evacuated Tubes solar still in comparison of Conventional still. It has been observed that theoretical outcomes from thermal modelling and the outcomes attained from experiments done for simple and modified stills are in respectable consensus.